AB0487 Scoring the correlations between nailfold microangiopathy severity and finger dermal thickness in systemic sclerosis patients. (23rd January 2014) - Sulli, A.; Ruaro, B.; Bernero, E.; Ferrari, G.; Pizzorni, C.; Cimmino, M. A.; Zampogna, G.; Cutolo, M.
Abstract : Background: Peripheral microangiopathy and increased dermal thickness (DT) are typical clinical aspects of systemic sclerosis (SSc) (1 -3 ). Objectives: The aim of this study was to identify and score possible correlations between nailfold microangiopathy severity and finger DT in systemic sclerosis (SSc) patients. Methods: Fifty-five SSc patients (mean age 54±12SD years, disease duration 6±5 years) and 42 healthy subjects were enrolled, after informed consent. All patients were evaluated by nailfold videocapillaroscopy (NVC) to classify and score the severity of microangiopathy. The appropriate NVC pattern was assigned to the SSc patients ("early", "active" and "late"), and the microangiopathy evolution score (MES) was also calculated (1, 4 -5 ). Both modified Rodnan skin score (mRss), and high frequency skin ultrasound (US), scored as PU, were employed to detect finger DT. US was performed at the level of the dorsum of the middle phalanx of the third finger on both right and left hand, and the average value of DT was recorded in millimetres. mRss was calculated at the level of the dorsum of the fingers bilaterally, as reported in the literature (6 ). Statistical analysis was carried out by non parametric tests. Results: SSc patients showed a statistically significant higher ultrasound-DT than healthy subjects, at the level of the fingers (p<0.0001). Ultrasound-DT was found progressively higher in SSc patients with the "early", "active" and "late" NVC patterns of microangiopathy (p=0.05). Furthermore, there was a statistically significant positive correlation between ultrasound-DT and MES (r=0.29, p=0.03). A positive correlation was also found between mRss and MES (r=0.57, p<0.0001), as well as mRss was found progressively higher in patients with "early", "active" and "late" pattern of microangiopathy (p<0.0001). A statistically significant positive correlation was observed between left and right finger ultrasound-DT (r=0.88, p<0.0001), as well as between ultrasound-DT and mRss (r=0.43, p=0.001). SSc patients with dcSSc showed higher mean values of ultrasound-DT than those with lcSSc (p=0.04). Furthermore, patients with dcSSc showed higher mRss and MES value than patients with lcSSc (p=0.0005 and p=0.004, respectively). Intra-operator variability in assessing DT by high frequency ultrasound technique was 6%. Conclusions: This study describes and scores for the first time the correlation existing between progressive impairement of microvasculature and amount of dermal tickness in SSc patients. References: Sulli A et al Arthritis Rheum. 2012; 64: 821-5. Moore TL et al. Rheumatology 2003; 42: 1559-63. Kaloudi O et al. Ann Rheum Dis. 2010; 69:1140-3. Sulli A et al. Ann Rheum Dis 2008; 67:885-7. Smith V et al. Ann Rheum Dis 2010; 69:1092-6. Clements PJ et al. J Rheumatol 1993; 20: 1892-6. Disclosure of Interest: None Declared